2014
DOI: 10.1084/jem.20131072
|View full text |Cite
|
Sign up to set email alerts
|

Improved HSC reconstitution and protection from inflammatory stress and chemotherapy in mice lacking granzyme B

Abstract: Granzyme B is expressed by hematopoietic stem cells (HSCs) and stromal cells in response to bacterial products or chemotherapy agents and limits HSC reconstitution potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…In addition, the increased expression of Gzmb may also contribute to HSPC damage, as Gzmb is induced by lipopolysaccharide and associated with increased cell death of HSPCs (Fig. C) .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the increased expression of Gzmb may also contribute to HSPC damage, as Gzmb is induced by lipopolysaccharide and associated with increased cell death of HSPCs (Fig. C) .…”
Section: Resultsmentioning
confidence: 99%
“…A significant IFN response was also obtained in the S11C). Note that the level of granzyme B expressed in the CD34 + cell population was 3 ± 1.2-fold higher in transplantations with unpurified UCB than with enriched CD34 + cells, suggesting that HSPCs experienced more stress (35) when mature immune cells were cotransplanted ( fig. S11D).…”
Section: Donor-derived Memory T Cells Secrete Tnfmentioning
confidence: 99%
“…Interestingly, a recent study showed that LPS induced granyzme B expression in LT-HSCs through the TLR4-TRIF-p65 NF-κB axis and granzyme B caused cell-autonomous apoptosis in HSCs [27*]. On the other hand, LPS induced cytokine production in ST-HSCs and MPPs through the TLR-p50 NF-κB pathway, leading to cytokine production and autocrine/paracrine signaling [11*].…”
Section: Regulation Of Stress-induced Hematopoiesis By Tlr Signalingmentioning
confidence: 99%